2022
DOI: 10.7717/peerj.13407
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping and candidate gene analysis of low temperature germination in rice (Oryza sativa L.) using a genome wide association study

Abstract: Low temperature germination (LTG) is a key agronomic trait in rice (Oryza sativa L.). However, the genetic basis of natural variation for LTG is largely unknown. Here, a genome-wide association study (GWAS) was performed using 276 accessions from the 3,000 Rice Genomes (3K-RG) project with 497 k single nucleotide polymorphisms (SNPs) to uncover potential genes for LTG in rice. In total, 37 quantitative trait loci (QTLs) from the 6th day (D6) to the 10th day (D10) were detected in the full population, overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Although the regulation of seed germination by GF14h was recently documented, its activity under low-temperature conditions remained unclear (Sun et al ., 2022; Yoshida et al ., 2022). While many genomic regions associated with LTG have been detected through QTL mapping and GWAS, only a few studies have identified the causal genes (Miura et al ., 2001; Fujino et al ., 2004; Han et al ., 2006; Jiang et al ., 2006; Fujino et al ., 2008; Nguyen et al ., 2012; Li et al ., 2013; Fujino et al ., 2015; Pan et al ., 2015; Satoh et al ., 2015; Jiang et al ., 2017; Shakiba et al ., 2017; Wang et al ., 2018; Jiang et al ., 2020; Shim et al ., 2020; Yang et al ., 2020; Pan et al ., 2021; Mao et al ., 2022). Indeed, LTG is a quantitative trait involving the cumulative effects of multiple genes and their epistatic relationships, making it difficult to assess the specific effect of a single genomic region on LTG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the regulation of seed germination by GF14h was recently documented, its activity under low-temperature conditions remained unclear (Sun et al ., 2022; Yoshida et al ., 2022). While many genomic regions associated with LTG have been detected through QTL mapping and GWAS, only a few studies have identified the causal genes (Miura et al ., 2001; Fujino et al ., 2004; Han et al ., 2006; Jiang et al ., 2006; Fujino et al ., 2008; Nguyen et al ., 2012; Li et al ., 2013; Fujino et al ., 2015; Pan et al ., 2015; Satoh et al ., 2015; Jiang et al ., 2017; Shakiba et al ., 2017; Wang et al ., 2018; Jiang et al ., 2020; Shim et al ., 2020; Yang et al ., 2020; Pan et al ., 2021; Mao et al ., 2022). Indeed, LTG is a quantitative trait involving the cumulative effects of multiple genes and their epistatic relationships, making it difficult to assess the specific effect of a single genomic region on LTG.…”
Section: Discussionmentioning
confidence: 99%
“…LTG is a quantitative trait regulated by complex molecular mechanisms. Linkage mapping and genome-wide association studies (GWAS) have identified over 30 LTG-related quantitative trait loci (QTLs) or genomic regions associated with this trait, located on all 12 rice chromosomes (Miura et al ., 2001; Fujino et al ., 2004; Han et al ., 2006; Jiang et al ., 2006; Fujino et al ., 2008; Nguyen et al ., 2012; Li et al ., 2013; Fujino et al ., 2015; Pan et al ., 2015; Satoh et al ., 2015; Jiang et al ., 2017; Shakiba et al ., 2017; Wang et al ., 2018; Jiang et al ., 2020; Shim et al ., 2020; Yang et al ., 2020; Pan et al ., 2021; Mao et al ., 2022). However, only a few genes involved in LTG have been described, such as qLTG3-1 (Fujino et al ., 2008) and STRESS-ASSOCIATED PROTEIN16 ( OsSAP16 ) (Wang et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [57][58][59][60][61][62][63][64][65][66][67][68][69][70] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Genome‐wide association studies (GWAS) are useful for identifying genes associated with complex traits (Huang et al, 2010) and have been applied successfully to the identification of LTG‐related loci (Fujino et al, 2015; Mao et al, 2022; Schläppi et al, 2017; Thapa et al, 2020; Wang, Lee, et al, 2018; Wang, Zou, et al, 2018; Yang, Yang, et al, 2020; Yang, Zhou, et al, 2020). Fujino et al (2015) identified 17 LTG‐related QTLs in a GWAS with 63 accessions and 117 markers, while Thapa et al (2020) used a GWAS with 257 accessions and an array of 7000 SNP markers to identify a large number of QTLs.…”
Section: Introductionmentioning
confidence: 99%
“…Fujino et al (2015) identified 17 LTG‐related QTLs in a GWAS with 63 accessions and 117 markers, while Thapa et al (2020) used a GWAS with 257 accessions and an array of 7000 SNP markers to identify a large number of QTLs. Further GWAS studies that identified LTG‐associated QTLs are those of Yang, Yang, et al (2020), Yang, Zhou, et al (2020) and Mao et al (2022).…”
Section: Introductionmentioning
confidence: 99%